2007
DOI: 10.1071/ch07157
|View full text |Cite
|
Sign up to set email alerts
|

Bisamidoximes: Synthesis and Complexation with Iron(III)

Abstract: Bisamidoximes have been synthesized by the reaction of 4-methylbenzohydroximoyl chloride with 1,2-diaminoethane, 1,3-diaminopropane, 1,4-diaminobutane, and 3,3′-diamino-N-methyl-dipropylamine. A monoamidoxime and a trisamidoxime were also prepared in the present work by the reaction of 4-methylbenzohydroximoyl chloride with N,N-dimethylethylenediamine and tris(2-aminoethyl)amine. Single crystal X-ray structures of three of the bisamidoximes have shown that the two amidoxime moieties have the Z configuration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…The band at 600 nm became less pronounced, and the absorbance at any other wavelength between 400 and 600 nm increased, with the latter also being observed for the free Fe­(III) control, hence indicating the presence of some noncomplexed Fe­(III) in the 0.5:1 solution. Overall, this suggests that the P­(EtOx 35 - stat -AO-BuOx 21 ) reached its limit to chelate Fe­(III) in a ratio of approximately 1:0.5, which is in good agreement with previous reports on small molecules . It is noteworthy that the excess Fe­(III) did not precipitate upon pH adjustment, suggesting a stabilization of the metal ions by the complexes. , This qualitative investigation demonstrated that the AO-modified POx can form metal complexes with Fe­(III) and that P­(EtOx 35 - stat -AO-BuOx 21 ) could have the potential for the treatment of excessive iron levels.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The band at 600 nm became less pronounced, and the absorbance at any other wavelength between 400 and 600 nm increased, with the latter also being observed for the free Fe­(III) control, hence indicating the presence of some noncomplexed Fe­(III) in the 0.5:1 solution. Overall, this suggests that the P­(EtOx 35 - stat -AO-BuOx 21 ) reached its limit to chelate Fe­(III) in a ratio of approximately 1:0.5, which is in good agreement with previous reports on small molecules . It is noteworthy that the excess Fe­(III) did not precipitate upon pH adjustment, suggesting a stabilization of the metal ions by the complexes. , This qualitative investigation demonstrated that the AO-modified POx can form metal complexes with Fe­(III) and that P­(EtOx 35 - stat -AO-BuOx 21 ) could have the potential for the treatment of excessive iron levels.…”
Section: Resultssupporting
confidence: 90%
“…AOs have two p K a values, (i) p K a1 ≈ 6 and (ii) p K a2 ≈ 13, which correspond to the protonated oxime nitrogen and oxime hydroxy group, respectively. , Thus, at physiological pH, the AO group exists in its neutral form bearing an oxime and amino group. Studies on AO-containing small molecules have revealed these to act as bidentate ligands in organic solvents. , To determine the complexation potential of the present systems in an aqueous environment, qualitative tests with different ratios of Fe­(III) to AO were performed. To allow for an efficient Fe­(III) complexation, metal-to-ligand ratios below 0.5:1 were studied under the assumption that two AO moieties will complex one Fe­(III) ion .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, different results on the Z/E configuration were obtained for the amidoxime fragment. In particular, it was found that in the case of compound 2, the calculated data are in agreement with the experimental results of the study of the Z,Zisomerism of bisamidoxime derivatives [40]. At the same time, according to the calculated DG values, the E-isomer of the amidoxime residue is predominated for compounds 3, 7-9, which is consistent with a stabilization of the amidoxime fragment in the aprotic solvent DMSO [36].…”
Section: Scheme 2 a Plausible Mechanism For The Formation Of Minor Psupporting
confidence: 84%